Democracia e planejamento urbano na revisão do Plano Diretor de Fortaleza (2002-2008) - Eduardo Gomes Machado (Reflexión Política, 2014)
Between 2002 and 2008 there was a revision of the Master Plan of F ortaleza. The Juraci Magalhães management produced a plan that was never voted, contested by agents who criticized the lack of democratization and popular participation. The management Luizianne Lins restarted the review , generating a plan approved by consensus. This article analyzes the institutional design, the formation of decisions and potential democratic character of these experiences. The methodology involved analysis of documents and videos, direct observation and conducting semi- structured interviews. It is estimated that there were important democratic innovations. However , the innovations non-impacted the institutional structures, making it insufficient to permanently change the correlations of strength, the rules and social behaviors in urban planning in the city .